Acylated Iridoids and Rhamnopyranoses from Premna odorata (Lamiaceae) as Novel Mesenchymal–Epithelial Transition Factor Receptor Inhibitors for the Control of Breast Cancer. (15th August 2017) - Elmaidomy, Abeer H.; Mohyeldin, Mohamed M.; Ibrahim, Mostafa M.; Hassan, Hossam M.; Amin, Elham; Rateb, Mostafa E.; Hetta, Mona H.; El Sayed, Khalid A.
Abstract : Phytochemical investigation of Premna odorata Blanco, Lamiaceae, leaves afforded three new acylated iridoid glycosides 1–3 and two new acylated rhamnopyranoses 9 and 10, in addition to ten known compounds. The structures of the new compounds were confirmed using extensive 1D and 2D NMR analysis. Molecular modeling study suggested the potential of the acylated rhamnopyranoses to bind at the c‐Met kinase domain. Cell‐free Z′‐LYTE™ assay testing revealed the good c‐Met phosphorylation inhibitory activity of 9, followed by 8, and 10, with IC50 values of 2.5, 6.9, and 12.7 μM, respectively. The (3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) cell proliferation assay testing against the human c‐Met expressing highly invasive MDA‐MB‐231 suggested compound 9 as the most active with IC50 value of 13.3 μM. Testing of compound 9 against multiple phenotypic breast cancer cell lines including MCF‐7, BT‐474 cells, and MDA‐MB‐468 proved enhanced activity against the highly c‐Met expressing triple‐negative breast cancer cell lines. Acylated rhamnopyranoses are potential novel c‐Met inhibitors appropriate for future optimizations to control c‐Met‐dependent breast malignancies. Copyright © 2017 John Wiley & Sons, Ltd.